PERENCANAAN INSTALASI PENERANGAN PADA GEDUNG FAKULTAS BIOLOGI UNIVERSITAS JENDERAL SOEDIRMAN - Kartika, Kartika; Nugroho, Daru Tri; Zulfa, Mulki Indana (Berkah Tematik Mandiri, 2024)
The Biology Faculty Building at Jendral Soedirman University is one of the new buildings that will be built by Jendral Soedirman University. The building is still in the planning process and has 3 floors with different rooms. This final project research uses the literature study method to analyze various aspects related to building electrical installations including calculating the index for each room, calculating lighting requirements, calculating total lighting power, determining the cross-sectional area of ​​cables, and calculating the current carrying capacity (KHA) requirements that will be used for the building. Faculty of Biology, Jendral Soedirman University. Calculation analysis will be carried out using Microsoft Excel 2016 software and the results will be adjusted to the General Requirements for Electrical Installation (PUIL) 2000 standards. Apart from that, the electrical installation design process also uses AutoCad 2021 software. The results of the planning analysis will be used as a guide for implementing building construction. The aim of this final project research is to plan a lighting installation system that is important for learning and teaching needs, as well as prioritizing comfort for students and lecturers. Therefore, the lighting installation system must also comply with the 2000 General Electrical Installation Requirements (PUIL) standards.